Exercise training inhibits left ventricular collagen upregulation in mice with hypertrophic cardiomyopathy. (14th October 2021) - Andreassen, K; Rixon, C L; Hasic, A; Hauge-Iversen, I M; Christensen, G; Haugaa, K H; Sjaastad, I; Edvardsen, T; Lunde, I G; Stokke, M K
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is estimated to affect 1:500, and is characterised by otherwise unexplained left ventricular (LV) hypertrophy, cardiomyocyte disarray, fibrosis, diastolic dysfunction, and ventricular arrhythmias. Historically, patients with HCM have been discouraged from participation in high intensity sports and exercise. However, the 2020 Sports Cardiology Guidelines recommend that patients with HCM should receive advice about exercise training (ET) based on individual risk assessment. To learn more about the effects of ET in HCM, we exposed mice carrying an HCM-causative sarcomere mutation (Myh6R403Q/+ (R403Q) mice) to high intensity interval training. Purpose: To investigate the effect of exercise training on hypertrophic cardiomyopathy in mice. Methods: R403Q mice were stratified to treadmill exercise (n=11) or sedentary behaviour (n=11). After 3 weeks, we induced HCM by giving CsA in the feed for 3 weeks, while the ET or sedentary behaviour continued for a total of 6 weeks. Each bout of treadmill running consisted of a 10-minute warm up, followed by 5 intervals of 8 minutes at high intensity (90% of VO2 max speed at week 0) and 2 minutes at medium intensity (60% of VO2 max speed at week 0). Every third day of the ET protocol we increased the high and medium intensity running speeds by 0.6 and 0.4 m/min, respectively. We performed echocardiography after 0, 3, and 6 weeks of the 6-week protocol. After completion of the protocol, we recorded lung and whole heart weight, and harvested LVs for molecular analyses. Results: Confirming the expected HCM phenotype, R403Q mice that received CsA (R403Q SED+CsA) had a 1.3-fold increase in whole heart weight (p<0.0001), 1.5-fold increase in lung weight (p<0.001), and 2.4-fold increase in maximal left ventricular posterior wall (LVPW) thickness measured by echocardiography (p<0.0001) compared to sedentary wild type littermates given CsA (WT SED+CsA). Heart weight, lung weight, and maximum LVPW thickness were also increased 1.5- (p<0.0001), 1.6- (p<0.0001), and 2.0-(p<0.0001) fold, respectively, compared to R403Q not given CsA (R403Q SED-CsA). R403Q ET+CsA mice increased their running distance before exhaustion 2.0-fold compared to baseline (p=0.010), and ran 1.6-fold longer than R403Q SED+CsA (p=0.020). In R403Q ET+CsA mice, LV mRNA expression of Col1a2 was 51% (p=0.021), and Col3a1 49% (p=0.013) of R403Q SED+CsA expression levels. Compared to R403Q SED+CsA mice, exercise training did not affect heart weight, maximum LV posterior wall thickness or lung weight in R403Q ET+CsA mice. Conclusion: Treadmill ET inhibited upregulation of LV collagen expression in mice with HCM, but did not affect hypertrophy. This could indicate that ET during early development of HCM attenuates development of fibrosis. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): South-Eastern Norway Regional Health Authority (Helse Sør-Øst RHF) and KG Jebsen Cardiac Research Center